(untitled) (Research, Society and Development, 2020)
Introduction: Violence against women is defined as the cause and suffering due to the condition of women. This directed characterization or problem for a gender construction, because the situations experienced by women are prohibited by the female class, built in the relations between men and women in the society in which they are inserted. Objective: To carry out a systematic review of the literature of the last five years based on the activities of prevention, control, approach and conduction of gender violence in the Family Health Strategy. Method: Articles published between 2014 and 2019 and indexed in the Virtual Health Library (VHL) database were selected for this systematic review. A search strategy used was initiated from the keywords (DeCS): "Violence", "Gender", "Public health" and "Brazil", also including the following limits: articles in Portuguese, English and Spanish , available in full. Then, the works were submitted to the PRISMA protocol for systematic reviews. Results: Gender-based violence is considered as a demand by professionals from FSE units. However, studies show that these professionals face difficulties in addressing issues such as users and some, never questioned about this issue. Conclusion: The qualification of health professionals with gender violence can make a positive contribution to care practice.